Prevalence and genomic insights into type III-A CRISPR-Cas system acquisition in global Staphylococcus argenteus strains - Xinhai Chen; Xinhai Chen; Li Xu; Li Xu; Zhijiang Luo; Zhijiang Luo; Lihong Wang; Lihong Wang; Zhenyu Wang; Zhenyu Wang; Zhenyu Wang; Yang Li; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionThe CRISPR-Cas system serves as a defense mechanism in bacteria and archaea, protecting them against the invasion of mobile genetic elements. Staphylococcus argenteus, a Gram-positive bacterium that diverged from Staphylococcus aureus, is characterized by the rare presence of the CRISPR-Cas system in only a few isolates. MethodsIn this study, we analyzed the prevalence of the type III-A CRISPR-Cas system in 368 S. argenteus genome sequences from animals, food sources, and humans across 26 countries, available in public database. ResultsOur findings revealed that 44.0% of these strains carry this immune system, with 98.1% of them belonging to the sequence type 2250 (ST2250). Genomic localization analysis indicated that the CRISPR-Cas is closely associated with SCCmec (mecA-ΔmecR1-IS1272-ccrB2-ccrA2) or Insertion sequence 1272 (IS1272) transposase. Further analysis identified a common IS1272 target inverted repeats (IR) sequence in ST2250 strains, providing insights into why these strains are more likely to acquire the CRISPR-Cas system. CRISPR typing identified 41 sequences types, classifying these strains into two clusters, with Cluster II being the predominant one. Homology analysis of spacers revealed that all the identified 15 spacers exhibited homology to sequences from plasmids, lytic phages, or prophages. ConclusionThis study suggests that the acquisition of the CRISPR-Cas system in S. argenteus enhances its resistance to phage attacks and plasmid invasions in environmental settings, potentially posing significant challenges for clinical treatment of infections caused by these strains and hindering efforts to control their spread in food products using phage-based interventions.